Estratificação vertical e checklist de Membracidae (Hemiptera: Auchenorrhyncha) em floresta úmida na Paraíba - Silva, Aline Lourenço Vieira da (2017)
Membracidae gathers phytophagous hemiptera of the suborder Auchenorryncha, presents world distribution and current has more than 3,500 described species. The treehopeers are mainly found in the tender parts of plants exposed to the sun and have interactions with several host plants and hymenoptera, on which they base the mutualistic relationship. The knowledge about the group is mostly concentrated in the area of systematics and taxonomy, although more recent studies also address aspects of ecology and natural history. In general, vertical stratification with insects has been developed in rain forests, but nothing is known about the vertical distribution patterns of the treehoppers species and the mechanisms determining these variations in tropical forests. In order to verify how the treehoppers are distributed in the different forest layers (canopy, medium and lower) in the areas of the Atlantic Forest of Paraíba, collections were made between June/2015 and March/2016 with yellow sticky cards at three heights (=15m, 8-10m and 1,5m) in four fragments in the state: RVS Mata do Buraquinho, RPPN Engenho Gargaú, REBIO Guaribas and RPPN Fazenda Pacatuba. In total, 1,205 treehoppers belonging to 67 species and 37 genera were collected, distributed among the different strata and fragments. The canopy was the richest stratum in all the sampled areas and presented the highest estimates of richness for both Chao 1 and Chao 2 estimators (85.03 ± 19.24, 95 ± 24.44). The ANOVA test showed a significant difference in richness only between the canopy and lower strata (F = 10.29; p = 0.00473). The results indicate that the taxocenosis of the treehoppers of the Atlantic Forest of Paraíba presents vertical distribution in two strata (Canopy and Inferior). The use of scientific collections allows the development of diverse works within the ecology, biography, conservation and systematics of the most different groups. An entomological collection of the Departamento de Sistemática e Ecologia (DSEC) of the UFPB began with an entry of some numbers without end of the 70s by Professor Dr. Pi Daniel and since then has increased its collection in different groups, such as Coleoptera, Hymenoptera, Diptera and Hemiptera. In order to know the biodiversity of Membracidae deposited in this collection, a checklist of the group for the Atlantic Forest of Paraíba was carried out. The specimens deposited in the DSEC collection were duly organized, numbered, and identified at the lowest possible taxonomic level with the aid of specific bibliography, bank pictures of different types of authors, and assistance of specialists in the group. In total, 4,820 individuals from the Atlantic Forest of Paraíba, from 10 counties: Areia, Cabedelo, Conde, Cruz do Espírito Santo, João Pessoa, Mamanguape, Mataraca, Mulungu, Santa Rita and Sapé were analyzed; with representatives of 68 species, seven species to be conferred "cf", 47 species identified at the generic level and two at the tribal level. The occurrence distribution of six species was extended to Brazil or Paraíba: Anobilia nigra Tode, Anobilia splendida Tode, Todea cf. incerta (Tode), Amastris funkhouseri Haviland, Neotynelia vertebralis (Fairmaire) and Leioscyta spiralis Haviland. It is necessary that existing scientific collections be expanded and maintained in ideal conditions so that more studies can be developed and bring a better understanding of Brazilian biodiversity, especially in the Northeast region of Brazil.